The Unmet Needs of Palliative Care Among Young and Middle-Aged Patients with Advanced Cancer: A Qualitative Study - Renhui Wen; Xinyi Liu; Yu Luo (Current Oncology, 2025)
Objective: This study aimed to explore the unmet palliative care needs among young and middle-aged (YMA) Chinese patients with advanced cancer. Methods: We used the principle of maximum difference. A total of 16 YMA patients with advanced cancer from cancer hospital were recruited. Semi-structured, in-depth, and face-to-face interviews were conducted from 28 August 2023 to 23 October 2023. The recorded audio of each interview was typed into Word software with each personal code. The interview transcripts were coded using the method of inductive content analysis. Results: Four themes and 14 sub-themes were identified in participants’ descriptions of care needs: (1) symptom management needs: need for pain relief, need for anti-emetics, and need for aid in managing fatigue; (2) psychological support needs: help reducing fear of pain, help achieving a better death, and help with parents’ negative reactions; (3) social support needs: taking care of children, emotional support from family members, consultation and emotional support from other cancer patients, and company and guidance of healthcare personnel; (4) information needs: better understanding of disease trajectory and future care needs, better access to palliative care information, and more participation in medical decision-making. Conclusions: According to the results of this study, the unmet palliative care needs of YMA patients with advanced cancer are diverse, but they have not been fully recognized and met. Therefore, medical staff should develop effective management strategies and explore patients’ needs in an all-around way. Future studies will further develop the scale of unmet needs for palliative care to accurately identify needs and improve patients’ quality of life.